ФОРМИРОВАНИЕ НАВЫКОВ ИНФОРМАЦИОННОГО САМООБСЛУЖИВАНИЯ БУДУЩИХ СПЕЦИАЛИСТОВ КУЛЬТУРЫ И ИСКУССТВА В УСЛОВИЯХ ВНЕДРЕНИЯ СТАНДАРТОВ ТРЕТЬЕГО ПОКОЛЕНИЯ: ОПЫТ ПРОЕКТНОГО РАЗВИТИЯ (Библиосфера, 2011)
The project activity of the State Universal Scientific Library of Krasnoyarsk Region on developing the Training-center is analyzed. The center is aimed to organize seminars-trainings for students of higher schools in cooperation with the Siberian Federal University.